STUDY ON LIFE PREDICTION AND FATIGUE TEST OF ZM6 MATERIAL WITH IMPACT PIT - LI Jian; YANG SuSong; YANG XianKun; WAN ZhenHua; HU WeiPing (Jixie qiangdu)
The smooth specimens,notched specimens and impact crater specimens of ZM6 material were prepared. The fatigue test of these specimens was carried out,and the fatigue life of these specimens under different stress levels was obtained.Based on the theory of continuum damage mechanics,a new multi-axial fatigue damage evolution model is proposed to describe the fatigue damage of local material with impact pits. ABAQUS was used to simulate the formation process of the impact pit crater,and the geometry of the pit crater and the local residual stress-strain field were obtained. By using the ABAQUS subroutine USDFLD,the material constitution and damage evolution were coupled,so as to realize the calculation of the fatigue life of the structure with impact pit crater. The results shows that the predicted median life was consistent with the test median life,and the error was within twice the error band,white meet the requirements of the engineering application.